AKADEMI KOMUNITAS DAN PENERAPAN MASTER PLAN PERLUASAN DAN PERCEPATAN PEMBANGUNAN EKONOMI INDONESIA (MP3EI) - Iskandar Agung (Jurnal Ilmiah Visi, 2014)
The establishment of Community Academy (CA) as a vocational education diploma one and/or two stipulated in Law No. 12/2012 fit 59 is an effort to increase the Gross Enrollment Ratio (GER) for higher education (HE), to develop human resource quality, and to provide an opportunity for the region to have a public university. In addition, the establishment of CA is expected to support the implementation and expansion of regional economic growth, as set out in the MP3EI concept initiated by the government. However, the results obtained by the study, the establishment of CA is still reaping a number of problems related to determining the course, the accuracy of the location of the appointment and organization of the study program, and the pattern of development and the ongoing working relationship. Having critically analyzed the problems, this article recommends to (a) conduct an in-depth and thorough assessment to determine the program of study in CA; (b) negotiate the establishment of CA with ‘assignment’ type and provide the opportunities for private sector CA to participate; (c) substitute the courses conducted by CA in certain regions ; (d) change the distribution budgent patterns: and (e) set a special teamwork responsible directly to the Minister of Education and Culture.